Uji Aktivitas Ekstrak Etanol 70% Daun Kaliandra Merah (Calliandra calothyrsus Meisn.) sebagai Penurun Kadar Glukosa Darah pada Tikus Hiperglikemia - Dwitiyanti Dwitiyanti; Hayati Hayati; Sindi Anggraeni (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
Diabetes mellitus (DM) is an increase in blood glucose levels due to impaired metabolism of carbohydrates, fats, and proteins. Red kaliandra leaf (Calliandra calothyrsus Meisn.) contains tocopherol, carotenoid, ﬂavonoid, saponin, and tannin compounds are natural sources of non-enzymatic antioxidants. The active compound has inhibitory activity against the α-glucosidase enzyme so that it can be potential as an antidiabetic. This study aims to determine the activity of 70% ethanol extract of red calliandra leaves on the decrease in blood glucose levels in male white rats Sprague Dawley hyperglycemia strain. Test animals were divided into 6 groups consisting of normal controls (standard feed), negative controls (alloxan induction), positive controls (metformin HCL dose 51.38 mg/kg), group I dose (50 mg/kg), dose II (100 mg/kg), and dose III (200 mg/kg). Data were analyzed using one way ANOVA and continued by Tukey test. The results showed that doses 1, 2, and 3 can reduce blood glucose. Dose 3 had a decrease in the percentage of 58.08% which was comparable to a positive control (metformin HCl dose 51.38 mg/kg) of 63.85%.